Review on the role of soil and water conservation practices on soil properties improvement in Ethiopia - Anteneh Asfaw (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Soil erosion is one of several major deterioration processes which result in soil degradation and declining agricultural productivity in Ethiopia due to the dense population, high livestock density, and intensive crop production in the area. Soil and water conservation practices are one of the mechanisms used to reduce erosion and associated nutrient loss, reducing the risk of production. Therefore, the review focuses on the importance of soil and water conservation practices on soil properties in Ethiopia. Several studies conducted in various parts of the country showed that the implemented soil bund reduced annual runoff and soil loss at different rates. Soil and water conservation have improved the soil Physico-chemical properties on conserved cropland (BD, SMC, pH, CEC, av. K, av. P, SOC, and TN) compared to the adjacent cropland without soil and water conservation measures. Soil and water conservation, reduce the removal of fertile topsoil and improves soil moisture, which favors crop growth as a result grain yield of the crops was increased. In general, the use of soil and water conservation strategies had clearly shown a positive impact on soil physico-chemical properties and crop yields. Therefore, to reduce soil erosion sustainably, different soil and water conservation options should be introduced and used considering agroecology, socio-economic profile, and climatic condition of the intervention area.